Comparison of four different pain scales in the evaluation of postoperative acute pain intensity - GÜRKAN, AYSEL (CUKUROVA UNIV, FAC MEDICINE, 2020)
Purpose: This study was conducted in order to compare the level of compliance and patient preferences among the Visual Analogue, Numerical Rating, Verbal Descriptor and Facial Pain Rating scales that are commonly used in adults, including the elderly. Materials and Methods: The study was conducted using a descriptive research model at the surgery clinics of a university hospital between March 17 and June 17, 2016. A total of 120 adult patients, being 40 in each group, were included in the study. Individual Characteristics Form, Visual Analogue Scale, Numerical Rating Scale, Verbal Descriptor Scale and Facial Pain Scales were used to collect the data. Result: In this study, the correlation coefficients between 0.71 - 0.83 and four pain scales were found to be in conformity with each other. Numerical Rating Scale was the most simple scale that was preferred to be used in the future by all patients with the least error rate, while the Visual Descriptor Scale was the least simple and least preferred scale by the patients with the highest error rate. The most simple and more preferred scale to use by young and middle-aged patients was the Numerical Rating Scale, while the elderly selected the Visual Descriptor Scale as the most simple and more preferred scale to use. Conclusion: The four scales are in good agreement with each other and Numerical Rating Scale is the first choice, the Verbal Descriptor Scale is the second choice, and the Visual Analogue Scale is the last choice in evaluating the postoperative acute pain intensity.
Keywords: Postoparatif pain; pain assessment; pain scales; PSYCHOMETRIC PROPERTIES; RATING-SCALES; MANAGEMENT; YOUNGER; PREFERENCES; ADULTS